(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study investigates the potential of Romanticism Literature to enhance cultural intelligence (CQ) and emotional intelligence (EQ) among learners of English as Foreign Language (EFL), addressing a gap in empirical research. Employing a qualitative methodology, the research surveyed 48 Algerian EFL students, following a six-week instructional period using texts by authors like Wordsworth, Blake, and Poe. The findings reveal a significant positive impact; participants reported a profound increase in cultural awareness, empathy towards other cultures, and comfort in emotional expression. Group discussions emerged as the most effective pedagogical tool for fostering these skills. The study concludes that integrating Romanticism literature is a transformative classroom strategy, effectively preparing students with the crucial intercultural and emotional competencies required in a globalized world.